Analisis faktor-faktor yang Mempengaruhi Pemilihan Platform Marketplace Akibat Penutupan Tiktok Shop: Studi Kasus Gen Z di UPI Kampus Tasikmalaya - Miizan Nur Qisthi; Adam Pratama Yudya Putra; Muhammad Athallah Khairi Arief; Rafaeza Athhar Ramadhan; Laras Bellaning Restu; Adi Prehanto; Asep Nuryadin (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explores the factors influencing consumers to switch from TikTok Shop to other marketplace platforms. Based on interviews with five respondents, it was found that cheaper prices, discounts and promotions, and features similar to TikTok Shop are the main factors influencing their decisions. These findings provide new insights into consumer behavior in choosing marketplace platforms, especially in the context of the closure of TikTok Shop. Keywords: TikTok Shop, marketplace platforms